Đặc điểm khoáng vật - địa hóa vỡ tuổi thành tạo của quặng hóa vàng Bồng Miêu - Anh, Trần Tuấn; Hòa, Trần Trọng; Borisenko, A. S.; Phượng, Ngô Thị; Dung, Phạm Thị; Anh, Trần Việt (Vietnam Journal of Earth Sciences, 2008)
Mineralization characteristics and age of formation of the Bong Mieu gold ore